ON THE DURABILITY OF CENTRIFUGAL PUMPS - Marius STAN (Fiabilitate şi Durabilitate, 2018)
Vibration diagnosis has developed rapidly, the practice of applying it proving to be highly effective, along with the development of measurement and signal processing techniques. Vibration diagnosis is preferred, with rare exceptions, to noise diagnosis, which is too much affected by ambient noise sources, requiring either special methods or devices or special measurement conditions. Vibrodiagnose, is one of the applications of fault diagnosis methods through vibration analysis to centrifugal pumps